DIMENSI SUFISTIK DANARTO DALAM CERPEN “O, JIWA YANG EDAN”: TINJAUAN SEMIOTIK - Sekar Nugraheni; Ali Imron Al-Ma'ruf; Main Sufanti (Kajian Linguistik dan Sastra, 2007)
The purpose of this research is to describe the dimension of sufistic in of shortstory “O, Jiwa yang Edan” masterpieces of Danarto with semiotic evaluation. Theresult of the sufistic dimension in a short story “O, Jiwa yang Edan” is on thetasawuf, terminology, understanding and hierarchy in tasawuf. At tasawuf hierarchythere are four steps which much be passed by that: (1) syari’at, (2) tarikat, (3)hakikat, and (4) makrifat. In the short story of “O, Jiwa yang Edan” the four stepsstarted from the tarikat described by leaving of enjoyment world. While the hakikatdescribed that any creature will go home to the God. Makrifat is if someone becometo recognize the reality of Allah. The understanding of tasawuf used by theauthor of short story is wahdatul syuhud.